Evaluation of pharmacological correction of endothelial dysfunction in children with Schonlein-Henoch purpura depending on the type treatment - Veronika M. Dudnyk; Tatiana G. Korol (Kazimierz Wielki University, 2015)
Dudnyk V. M., Korol T.G. Оцінка ефективності фармакологічної корекції ендотеліальної дисфункції у дітей з пурпурою Шенлейн-Геноха в залежності від виду лікування = Evaluation of pharmacological correction of endothelial dysfunction in children with Schonlein-Henoch purpura depending on the type treatment. Journal of Education, Health and Sport. 2015;5(3):189-198. ISSN 2391-8306. DOI: 10.5281/zenodo.16359 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A189-198 https://pbn.nauka.gov.pl/works/549869 http://dx.doi.org/10.5281/zenodo.16359 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015.   УДК: 616 - 005.151 - 053:611.018.74: 616 - 008.6:615.03   ОЦІНКА ЕФЕКТИВНОСТІ ФАРМАКОЛОГІЧНОЇ КОРЕКЦІЇ ЕНДОТЕЛІАЛЬНОЇ ДИСФУНКЦІЇ У ДІТЕЙ З ПУРПУРОЮ ШЕНЛЕЙН-ГЕНОХА В ЗАЛЕЖНОСТІ ВІД ВИДУ ЛІКУВАННЯ EVALUATION OF PHARMACOLOGICAL CORRECTION OF ENDOTHELIAL DYSFUNCTION IN CHILDREN WITH SCHONLEIN-HENOCH PURPURA DEPENDING ON THE TYPE TREATMENT   В.М.Дудник, Т.Г.Король V. M. Dudnyk, T.G. Korol   Вінницький національний медичний університет ім. М.І. Пирогова, кафедра педіатрії № 2 Vinnitsa National Medical University, Pediatrics department №2   Purpose evaluate the effectiveness of pharmacological correction of endothelial dysfunction in purple Schonlein - Henoch children depending on the type of treatment. Material and methods. Under the dynamic observation of the child was located 123 Schonlein purpura - Henoch aged 1 to 18 years (mean age 6,44 ± 0,18 years). Evaluation of immune response and endothelial dysfunction (IgG - ANCA (PR3), VEGF) was performed ELISA ELISA (solid phase ELISA) analyzer EUROIMMUN Analyzer 1 using the test - system EUROIMMUN (Germany) and a set of Human s VEGF R1 / Fit-1 in Medical Laboratory «Synevo» (the certificate №PU-0127/09 by 18.08.2009r.). Assessment of the functional state of the vascular endothelium and speed characteristics was performed using ultrasound Doppler ultrasound scanner in "Philips HDII XE" in B-mode sensor linear format in the frequency range from 5 to 15 MHz at rest.             The Results. Children who received basic therapy Schonlein purpura - Henoch, combined with polyoxidonium, observed a significant decrease in the content of serum biochemical markers of endothelial dysfunction and antyneytrofilnyh cytoplasmic antibody (VEGF, NO and ANCA within 27.2% - 43.6%) compared with those of children without the use polyoxidonium. Also, when you connect polyoxidonium observed a more pronounced improvement of the functional state of the vascular endothelium - the thickness KIM KIM CA and PA decreased by 30.8% and 48.4% compared with those of children who received only basic therapy. Keywords: Henoch - Schonlein purpura, children, endothelial dysfunction, рolyoxidonium.   Мета роботи - оцінити ефективність фармакологічної корекції ендотеліальної дисфункції при пурпурі Шенлейн - Геноха у дітей в залежності від виду лікування. Матеріал і методи. Під динамічним спостереженням знаходилось 123 дитини з  пурпурою  Шенлейн - Геноха віком від 1 до 18 років (середній вік 6,44±0,18 років). Оцінку показників імунологічної відповіді та ендотеліальної дисфункції (IgG - ANCA (PR3), VEGF) проводили імуноферментним методом ELISA (твердофазний ІФА) на аналізаторі EUROIMMUN Analyzer 1 за допомогою тест - системи EUROIMMUN (Німеччина) та набору Human s VEGF R1/Fit-1 в медичній лабораторії «Synevo» (свідоцтво про атестацію №ПУ-0127/09  від 18.08.2009р.). Оцінку функціонального стану судинного ендотелію та швидкісних характеристик проводили за допомогою ультразвукової доплерографії на УЗ-сканері "Philips HDII XE" в В-режимі датчиком лінійного формату в частотному діапазоні від 5 до 15 МГц в стані спокою.             Результати. У дітей, які отримували базисну терапію пурпури  Шенлейн - Геноха, поєднану з поліоксидонієм, спостерігалось більш суттєве зниження вмісту в сироватці крові біохімічних маркерів ендотеліальної дисфункції та антинейтрофільних цитоплазматичних антитіл (VEGF, NO та ANCA в межах 27,2% - 43,6%), порівняно з аналогічними показниками у дітей без застосування поліоксидонію. Також при приєднанні поліоксидонію відмічено більш виражене покращення функціонального стану судинного ендотелію - товщина КІМ СА та КІМ ПА зменшилась на 30,8% і 48,4%, порівняно з аналогічними показниками дітей, які отримували лише базисну терапію. Ключові слова: пурпура Шенлейн - Геноха, діти, ендотеліальна дисфункція, поліоксидоній.